Construction Waste Management in India: an exploratory study - Arif, M.; Bendi, D.; Toma-Sabbagh, T.; Sutrisna, Monty (Emerald, 2012)
Purpose – The growth of Indian economy has brought with it significant increase in construction activities. These increased construction activities have further highlighted the problem of waste generation on construction sites. The purpose of this paper is to provide important insights and highlight some issues related to the implementation of effective waste management practices on construction sites in India. Design/methodology/approach – This paper presents two cases and results from semi-structured interviews which shed light on some of the major issues, challenges and drivers associated with the implementation of waste management in construction in India. Findings – One of the key findings was that client preference and enforcement of existing laws could actually facilitate the implementation of waste minimisation effectively. Some of the practices being followed, and which are gaining more popularity, are waste quantification, waste segregation, and the implementation of 3Rs (reduce, recycle, and reuse). Congested construction sites, sites in heavily built-up areas with no ability to have an alternate storage or staging location for materials, lack of ownership of waste due to the presence of multiple contractors on the construction site and lack of awareness and education among the construction workforce were regarded as major challenges associated with the implementation of waste minimisation practices in India.Research limitations/implications – The cases and the interviewees chosen were through the authors' links with the Indian Green Building Council (IGBC). The cases were LEED registered projects therefore issues dealing with green construction had been taken into account. These cases might not be representative of the entire country, as there are significantly high proportions of construction projects that are not as green, especially in smaller cities in India. However, the two cases do provide important insights and highlight some issues related to the implementation of effective waste management practices on construction sites in India. The individuals interviewed also had link with IGBC. They had been involved with the green building movement in India for a significant length of time. But the length and breadth of their experience gave them the ability to comment on state of the construction sector and its green as well as non-green practices associated with waste management. Originality/value – This paper presents an exploratory study which assesses the implementation of waste management practices in the Indian construction industry. It also highlights activities within different stages of a construction project that can lead to more effective waste management in the construction sector.